2015
DOI: 10.4236/ojce.2015.51007
|View full text |Cite
|
Sign up to set email alerts
|

Case Study: Finding Better Solutions for Municipal Solid Waste Management in a Semi Local Authority in Sri Lanka

Abstract: This case study investigates better and sustainable waste management for a given area in Sri Lanka. A questionnaire and field surveys were performed in a small local authority adjacent to Colombo, the capital city. Composting for organic waste and incineration for non-compostable waste were found to be important treatment methods for solid-waste management. The reduction of solid waste is a critical process for sustainable management. Currently, people in the area do not have much interest in waste recycling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…The typical waste composition in Sri Lanka (Table 1) consists of high organic matter, a moderate amount of plastic and paper and a low content of metal and glass (Vidanaarachchi et al, 2006). Liyanage et al (2015) specified the other features of Colombo city’s MSW as 300–350 kg m −3 specific density, 55–65% moisture content and 600–1200 kcal kg −1 for calorific value. Based on the analytical results, the moisture content of the generated OFMSW in the Kaduwela area is 73.9 ± 1.05%.…”
Section: Resultsmentioning
confidence: 99%
“…The typical waste composition in Sri Lanka (Table 1) consists of high organic matter, a moderate amount of plastic and paper and a low content of metal and glass (Vidanaarachchi et al, 2006). Liyanage et al (2015) specified the other features of Colombo city’s MSW as 300–350 kg m −3 specific density, 55–65% moisture content and 600–1200 kcal kg −1 for calorific value. Based on the analytical results, the moisture content of the generated OFMSW in the Kaduwela area is 73.9 ± 1.05%.…”
Section: Resultsmentioning
confidence: 99%
“…In tackling waste management problems, Liyanage et al (2015) noted turning organic waste into compost and incinerating non-organic waste are important treatment methods for solid-waste management. Liyanage et al also found that reduction of solid waste is a critical process for sustainable management but people do not have much interest in waste recycling which has the potential to decrease the cost of solid-waste management.…”
Section: Waste Management Practicesmentioning
confidence: 99%
“…Household-level and community-based (decentralized) composting near to the source, is proven to be successful in most SAARC countries, including India, Sri Lanka, Nepal, and Bangladesh. Comparatively, centralized composting sites are less successful (Guerrero et al, 2013;Liyanage, Gurusinghe, Herat & Tateda, 2015;Zurbrügg, Drescher, Rytz, Sinha & Enayetullah, 2005). Moreover, in island nations such as the Maldives, composting of organic waste is mostly done in backyards of homes (Glawe, Visvanathan, & Alamgir, 2005).…”
Section: Recyclingmentioning
confidence: 99%
“…Unsuitable locations, public protests against odor and contamination of water bodies, marketing constraints are the reasons for the failure of centralized composting sites (Cofie et al, 2006;Hai & Ali, 2005;Liyanage et al, 2015). However, in some countries, composting is done in commercial level successfully.…”
Section: Recyclingmentioning
confidence: 99%
See 1 more Smart Citation